APLIKASI TQM PADA MANAJEMEN PERGURUAN TINGGI: SUDUT PANDANG KEPEMIMPINAN, KOMITMEN ORGANISASIONAL DAN MANAJEMEN SDM - Ramadhania, SE, MSi, M.Irfani Hendri, SE, MSi dan (Fakultas Ekonomi dan Bisnis, UNTAN, 2010)
This research is aimed at asessing Total Quality Management (TQM) application in higher education, especially at the faculty of economics, UNTAN resulting from competitive grant programme such as TPSDP, DUE-like and SP-4. Some aspects of TQM including leadership, organizational commitment dan human resource management employing 28 indicators are descriptively analysed. The results of study show that essentially the faculty of economics, UNTAN has put the TQM concepts in practice by conducting self-evaluation which is used as reference to making a programme of quality improvement in accordance with the RAISE++ principles. On average, using 11 indicators the score of leadership from the faculty staff members point of view is moderate with score of 3,55. Organizational commitment is regarded good with score of 4,36, whereas human resource management has the score of 3,55 and is regarded moderate. Keywords: Total Quality Management (TQM), Leadership, Organizasional Commitment, Human Resources Mangement.